Can we manage coastal ecosystems to sequester more blue carbon?. Issue 4 (10th April 2017) - Macreadie, Peter I; Nielsen, Daniel A; Kelleway, Jeffrey J; Atwood, Trisha B; Seymour, Justin R; Petrou, Katherina; Connolly, Rod M; Thomson, Alexandra CG; Trevathan‐Tackett, Stacey M; Ralph, Peter J
Abstract : To promote the sequestration of blue carbon, resource managers rely on best‐management practices that have historically included protecting and restoring vegetated coastal habitats (seagrasses, tidal marshes, and mangroves), but are now beginning to incorporate catchment‐level approaches. Drawing upon knowledge from a broad range of environmental variables that influence blue carbon sequestration, including warming, carbon dioxide levels, water depth, nutrients, runoff, bioturbation, physical disturbances, and tidal exchange, we discuss three potential management strategies that hold promise for optimizing coastal blue carbon sequestration: (1) reducing anthropogenic nutrient inputs, (2) reinstating top‐down control of bioturbator populations, and (3) restoring hydrology. By means of case studies, we explore how these three strategies can minimize blue carbon losses and maximize gains. A key research priority is to more accurately quantify the impacts of these strategies on atmospheric greenhouse‐gas emissions in different settings at landscape scales.